Elementos para análise e controle dos discursos no Processo Penal do Júri - Arcuri, Silvio José Farinholi (2023)
The legislator improved the language rules to be observed by the participants in the process, attributing to the judge the task of analyzing and controlling judicial discourses. In order to properly participate in the communicational situation of the criminal procedure, the jurist needs to have several skills, in order to understand what speech is and how it takes place, so as not to confuse it with mere acts of speech and thus know how to observe its rules and its scope paper in that order. As a “political-ideological man”, he must have the understanding that speaking is not simply saying something about the world, but acting in the world. Language as a discourse is power and social production, it has ideology, not being neutral or innocent to be reduced to the simple handling of grammar rules or the words of a dictionary, as is believed by common sense. Due to the absence of a legal criterion for the interpretation of judicial discourses, the concepts of Discourse Analysis were adopted, in the innovative perspective of this Thesis, duly adapted to the legal procedure. By the proposed method, applied to the ethos of the criminal procedure, steeped in its values and democratic principles, it was concluded that there are permitted and prohibited speeches for the staging of criminal cases. Prohibited speeches, because they cause disturbance, cannot be accepted in the communicative channels of criminal proceedings. They do not meet the criteria of ethical discourse, as they violate legal precepts (for example, in cases of use of an argument from authority or in offense to the dignity of victims and witnesses of crimes) and constitutional dictates, as occurs when practicing speeches of hate. The Theme 1087 of the Federal Supreme Court can be solved through the perception of a hybrid system of acquittals in the Jury Court, for legal and supralegal causes. Legal causes are justified by the evidence in the file and supralegal ones by respect for the rules of speech. The generic question should cover only supralegal causes and the analysis of its merits is exclusively up to the popular jury. Control of the legality of this decision may be exercised on appeal, based on nullity subsequent to the pronouncement